Teaching laboratory for large cohorts of undergraduates: Private and social information in fish - Jost Borcherding; Mike M. Webster; Katja Heubel (Ecology and Evolution, 2020)
Abstract A challenge in the Bachelor's studies in Biology is to strike a balance between reducing the teaching of practical scientific experiments to what is feasible in a short time, and teaching “real” science in undergraduate laboratories for high numbers of participants. We describe a laboratory in behavioral biology, with the primary focus on the student learning. However, also the underlying scientific question and the results of the experiment, namely the behavior of the three‐spined stickleback (Gasterosteus aculeatus) in a trade‐off situation during foraging, is without a doubt timely and sufficient for scientific studies on this subject, and this through the experiments conducted and data collected by the students. The students rated this laboratory well and learned at the end that social information is certainly important, but that self‐learning can be more important, and this not only in small fish, but also for the students themselves.